Upaya Unit Patroli Sabhara dalam Meningkatkan Pencegahan Curanmor Roda Dua: Sabhara Patrol Unit's Efforts to Improve Two-Wheeled Vehicle Theft Prevention - Sudding, Ananda Praditya (Police Studies Review, 2021)
This research was motivated by the rampant crime of curanmor in the Sumedang Police jurisdiction which was associated with efforts to improve the performance of the Sabhara Unit patrol unit in preventing crimes that occurred in the jurisdiction of the Sumedang Police. This study aims to describe the occurrence of two-wheeled curanmor (R2) in the jurisdiction of the Sumedang Police, the implementation of patrols by the Sabhara Unit of the Sumedang Police in preventing the crime of two-wheeled curanmor (R2), as well as the factors that influence the efforts of the patrol unit. This research was conducted using a qualitative approach, using field research methods, as well as data collection techniques by interview, observation, and document review. To discuss the problem the writer uses conceptual literature, namely the Sabhara concept, the patrol concept, management theory (George R. Terry), and performance theory (Armstrong and Baron). Existing data is then analyzed using data analysis techniques, namely data reduction, data presentation and drawing conclusions. The results showed that the preventive actions carried out by the Sabhara Unit through patrols were already running but were not yet optimal due to factors that hindered the patrol unit's performance, including the quantity and quality of personnel, facilities and infrastructure, patrol implementation methods, and leadership supervision. Efforts are needed to improve the performance of the Sumedang Police Sabhara Unit patrol unit by increasing the quantity and quality of personnel, supporting facilities and infrastructure, good implementation methods and increasing supervision of the implementation of patrols.